2022
DOI: 10.1021/acs.bioconjchem.2c00080
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Chemoproteomic Profiling of Targets of Au(I) Complexes by Competitive Activity-Based Protein Profiling

Abstract: Owing to the encouraging pharmacological action and acceptable toxicity profile, Au(I) complexes have attracted growing interest in the application of disease treatment. In order to investigate their potential target proteins and related bioinformation, herein, we screened four Au(I) complexes and explored the binding proteins utilizing a competitive activity-based protein profiling (ABPP) strategy, including identification experiments and reactivity classification experiments, which offers a simple and robust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Global chemoproteomic profiling revealed that itaconate covalently modified key cysteines in fructosebisphosphate aldolase A (ALDOA) and inhibited its enzyme activity, resulting in impairment of glycolytic flux and attenuation of the inflammatory response in stimulated macrophages. Moreover, considering cysteine often serves as a metal-chelating residue, this competitive method has also been exploited to identify metal-binding sites in proteomes, including zinc, [96] gold [97] and iron-sulfur cluster (FeÀ S). [98] In addition to endogenous metabolites, ABPP is a powerful strategy for target identification of natural products.…”
Section: Development Of Methods Derived From Isotop-abppmentioning
confidence: 99%
“…Global chemoproteomic profiling revealed that itaconate covalently modified key cysteines in fructosebisphosphate aldolase A (ALDOA) and inhibited its enzyme activity, resulting in impairment of glycolytic flux and attenuation of the inflammatory response in stimulated macrophages. Moreover, considering cysteine often serves as a metal-chelating residue, this competitive method has also been exploited to identify metal-binding sites in proteomes, including zinc, [96] gold [97] and iron-sulfur cluster (FeÀ S). [98] In addition to endogenous metabolites, ABPP is a powerful strategy for target identification of natural products.…”
Section: Development Of Methods Derived From Isotop-abppmentioning
confidence: 99%
“…92 The activity based-protein profiling approach is not limited to electrophiles. Several groups have developed probes to discover protein targets of metal complexes harboring gold, [93][94][95] arsenic, [96][97][98] and platinum. 99 An interesting discovery found using this approach in A549 cells is that strongly arsenicbinding proteins are dominated by anti-oxidant proteins such as thioredoxin and peroxiredoxin.…”
Section: B Activity-based Protein Profilingmentioning
confidence: 99%